Nightmare on Elm Street : Dream warriors - Russell, Chuck, 1952-; Craven, Wes.; Wagner, Bruce, 1954-; Langenkamp, Heather, 1964-; Englund, Robert, 1947-; Arquette, Patricia, 1968-; Badalamenti, Angelo ([Burbank, CA] : New Line Home Video, 2000)
The vicious Freddy Krueger haunts the dreams of the Elm Street Kids, now in a psychiatric ward, and dream researcher Nancy Thompson is the only one who can help them fight him on his own supernatural ground.
Originally released as a motion picture in 1987.
Director of photography, Roy H. Wagner; production design, Mick Strawn, C.J. Strawn; editors, Terry Stokes, Chuck Weiss; music, Angelo Badalamenti.
Heather Langenkamp, Patricia Arquette, Laurence Fishburne, Robert Englund, Priscilla Pointer, Craig Wasson.
MPAA rating: R.
DVD Dolby surround.
Closed-captioned.
Keywords: Krueger, Freddy (Fictitious character); Nightmares -- Drama; Nightmare on Elm Street films; Drama; Feature films; Horror films; Video recordings for the hearing impaired